Intelligence as a Psychological Mechanism for Ecotheory of Creativity. Issue 4 (2nd October 2019) - Luoto, Severi; Jonason, Peter K.
Abstract : Evolution causes biological and cultural diversity through adaptation to environmental conditions. This idea forms the cornerstone of recent research on the ecological origins of innovation and creativity, advanced prominently by Van de Vliert and Murray (2018) as the ecotheory of creativity . Van de Vliert and Murray propose that heat demands and cold demands impose different selection pressures on human creativity, which are further moderated by wealth resources. This commentary tests the hypothesis that population-level variation in intelligence serves as one of the mechanisms that links atmospheric cold demands to population-level variation in creativity. The results of a mediation analysis show that 70.7% of the cross-nationally significant effect of cold demands on national creative culture ( r  = .55, p  < .001, n  = 155 nations) is mediated by intelligence. This finding responds to Van de Vliert and Murray's research call for a more detailed understanding of the psychobehavioral mechanisms underpinning human adaptation to harsh environments. Overall, the results complement existing research which indicates that intelligence and cultural innovations may form two interlinked constituents of a suite of human adaptations or adaptive responses to cold climate.